¿Existe la naci?n puertorriquefia?: Este país no existe de Myrna Casas - Rivera, Carlos Manuel (Latin American Theatre Review, 2007)
From the 40s to the present, the theatre has served to present an academic debate about the Puerto Rican nation. The existence of Puerto Rico is not limited by the representation of a sovereign state but through cultural homogenization. Myrna Casas’ play Este pais no existe questions this debate by deconstructing the totalizing discourse of nationalism, which has eliminated differences in the society during the era of globalization and the consumer aspects of a spectacle society marked by simulacra. In this play the audience and the readers view the loss of Puerto Rican national values which were addressed in a Lettered Society. (CMR, in Spanish)